A meta-analysis of temporal shifts in environmental concern between 1994 and 2017: An examination of the new environmental paradigm. (June 2022) - Lou, Xiaobin; Li, Liman Man Wai; Xia, Weiwei; Zhu, Qishan
Abstract: Public environmental concern is important for social transformations to sustainability. Previous findings regarding the temporal trend of environmental concern yielded inconsistent results. Their methodological divergence, however, prevented further result integration or moderation analyses. This cross-temporal meta-analysis used the New Environmental Paradigm of human thinking (reflecting the perceived relationship between humans and the environment) as an indicator of environmental concern to examine its temporal trend and the factors moderating this trend. We analyzed 184 independent study samples using the original or revised New Environmental Paradigm Scale ( n = 73, 645 participants) from 47 countries/regions between 1994 and 2017. Results showed that the New Environmental Paradigm of thinking decreased over time. No reliable evidence supported that the study sample characteristics (i.e., student vs. nonstudent sample type, sample mean age, and gender ratio) or societal characteristics (i.e., geographical location, societal education, and societal wealth) moderated the declining trend. Despite limitations of including only convenience samples in the analysis, the findings imply a global decreasing trend of environmental concern. The findings highlight the urgent need for new, effective campaigns or interventions to reverse this trend. Highlights: We conducted a cross-temporal meta-analysis using 184 convenience samples. Environmental concern, measured by the New Environmental Paradigm, decreased. The decrease in environmental concern remained after controlling for confounders. No significant moderator was found to influence the declining trend.